Family intervention in a prison environment: A systematic literature review. (22nd April 2016) - Roberts, Anna; Onwumere, Juliana; Forrester, Andrew; Huddy, Vyv; Byrne, Majella; Campbell, Catherine; Jarrett, Manuela; Phillip, Patricia; Valmaggia, Lucia
Abstract: Background: The prison population in England and Wales is approximately 85, 000, and elevated rates of mental health difficulties have been reported among the prisoners. Despite frequent recommendations for family interventions to optimise prisoner outcomes, the evidence for its use and impact in prison remain unclear. Aim: The aim of the study is to conduct a systematic review of published literature on family interventions in prisons. Methods: Embase, PsychINFO and Medline were searched using terms for family interventions and for prisoners or young offenders. No limit was imposed on study design, but, for inclusion, we required that papers were written in English and published in peer‐reviewed journals. Results: Nine hundred eighty‐three titles were retrieved. Twenty‐two met criteria for inclusion. Three were case studies, 12 were descriptive, 6 were quasi‐experimental and one was a randomised controlled trial. Interventions and study methods were too heterogeneous for meta‐analysis. All studies gave positive conclusions about family interventions, but empirical data on effectiveness were slight. Conclusions: Consistency in findings across the wide‐ranging studies suggested that family therapies may indeed be helpful for prisoners and their families, so further research is warranted. The fact that a randomised controlled trial proved feasible should encourage researchers to seek more robust data and to determine which form of intervention is effective and in which circumstances. It would also be useful to develop an improved understanding of mechanisms of change. Copyright © 2016 John Wiley & Sons, Ltd.